2014
DOI: 10.1080/03601234.2014.894778
|View full text |Cite
|
Sign up to set email alerts
|

Chloromuconolactone dehalogenase ClcF of actinobacteria

Abstract: This work investigated the distribution of the clcF gene in actinobacteria isolated from different ecotopes. The gene encodes chloromuconolactone dehalogenase (CMLD) ClcF, the enzyme found to date in only one representative of Gram-positive bacteria, Rhodococcus opacus 1CP, adapted to 2-chlorophenol (2CP). Using primers specific to the clcF gene, from the DNA matrix of rhodococcal strains closely related to species Rhodococcus wratislaviensis (P1, P12, P13, P20, G10, KT112, KT723, BO1) we obtained PCR products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A previous study showed that the analysis of both whole cells of the R. opacus 1CP strain grown on 3-CBA and CMLD isolated from them revealed a peak with a mass of 11,193 Da [ 33 ], which corresponded well to the derived mass of CMLD, which indicated the formation of 3-CCat during the growth of this culture with 3-CBA ( Figure 4 ). Analysis of partially purified protein preparations of R. ruber P25 and M. foliorum B51 also produced corresponding mass peaks.…”
Section: Resultsmentioning
confidence: 72%
“…A previous study showed that the analysis of both whole cells of the R. opacus 1CP strain grown on 3-CBA and CMLD isolated from them revealed a peak with a mass of 11,193 Da [ 33 ], which corresponded well to the derived mass of CMLD, which indicated the formation of 3-CCat during the growth of this culture with 3-CBA ( Figure 4 ). Analysis of partially purified protein preparations of R. ruber P25 and M. foliorum B51 also produced corresponding mass peaks.…”
Section: Resultsmentioning
confidence: 72%